Epacadostat plus pembrolizumab versus placebo plus pembrolizumab as first-line treatment for metastatic non-small cell lung cancer with high levels of programmed death-ligand 1: a randomized, double-blind phase 2 study - Takaaki Tokito; Oleksii Kolesnik; Jens Sørensen; Mehmet Artac; Martín Lázaro Quintela; Jong-Seok Lee; Maen Hussein; Miklos Pless; Luis Paz-Ares; Lance Leopold; Jeannie Daniel; Mihaela Munteanu; et al. (BMC Cancer, 2024)
Abstract Background Pembrolizumab is a first-line therapy for certain patients with advanced/metastatic non-small cell lung cancer (NSCLC). Combining pembrolizumab with other immunotherapies may enhance tumor cell killing and clinical outcomes. Epacadostat is a selective inhibitor of indoleamine 2,3-dioxygenase 1, an immuno-regulatory enzyme involved in tryptophan to kynurenine metabolism that inhibits T cell-mediated immune responses. Methods In this randomized phase II study, patients with metastatic NSCLC expressing high (≥ 50%) programmed death-ligand 1 (PD-L1) levels received pembrolizumab 200 mg every 21 days plus oral epacadostat 100 mg twice daily (combination) or matching placebo (control). The primary objective was objective response rate (ORR); secondary objectives were progression-free survival (PFS), overall survival (OS), duration of response (DOR) and safety/tolerability. Results 154 patients were randomized (77 per group). Median (range) follow-up was 6.8 months (0.1–11.4) and 7.0 months (0.2–11.9) in the combination and control groups, respectively Confirmed ORR was similar between groups (combination: 32.5%, 95% CI 22.2–44.1; control: 39.0%, 95% CI 28.0–50.8; difference: − 6.5, 95% CI − 21.5 to 8.7; 1-sided P = 0.8000). Median (range) DOR was 6.2 months (1.9 + to 6.5 +) and not reached (1.9 + to 8.6 +) in the combination and control groups, respectively. Although not formally tested, median PFS was 6.7 and 6.2 months for the combination and control groups, respectively, and median OS was not reached in either group. Circulating kynurenine levels increased from C1D1 to C2D1 (P < 0.01) in the control group and decreased from C1D1 to C2D1 (P < 0.01) in the combination group but were not normalized in most patients. The most frequent serious adverse events (AEs) (≥ 2%) were pneumonia (4.0%), anemia (2.7%), atelectasis (2.7%) and pneumonitis (2.7%) in the combination group and pneumonia (3.9%), pneumonitis (2.6%) and hypotension (2.6%) in the control group. Two deaths due to drug-related AEs were reported, both in the control group. Conclusions Addition of epacadostat to pembrolizumab therapy for PD-L1–high metastatic NSCLC was generally well tolerated but did not demonstrate an improved therapeutic effect. Evaluating higher doses of epacadostat that normalize kynurenine levels when given in combination with checkpoint inhibitors may be warranted. Trial registration ClinicalTrials.gov, NCT03322540. Registered 10/26/2017.